Pengaruh Social Media Marketing Dan Brand Image Terhadap Keputusan Pembelian Jasa Pada Klinik Gigi Amary Bintaro Tangerang Selatan - Hasti Anggraeni; Nani Sriyani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the effect of Social Media Marketing and Brand Image, both partially and simultaneously, on Service Purchase Decisions at Amary Dental Clinic Bintaro, South Tangerang. This study uses a quantitative research method. The population in this study consists of consumers of Amary Dental Clinic Bintaro with a total sample of 99 respondents, and the sampling technique used is slovin. Data collection was carried out using questionnaires. The data analysis techniques used include validity testing, reliability testing, classical assumption testing, simple and multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing with the assistance of SPSS version 25. The results of the study indicate that Social Media Marketing has a positive and significant partial effect on Purchase Decisions, with the regression equation Y = 12.837 + 0.755X₁. The t-test results show a t-value of 12.785 > t-table. Brand Image has a positive and significant partial effect on Purchase Decisions, with the regression equation Y = 0.765 + 0.972X₂. The t-test results show a t-value of 34.808 > t-table. Social Media Marketing and Brand Image simultaneously have a positive and significant effect on Purchase Decisions, with the regression equation Y = 0.761 + 0.103X₁ + 0.886X₂.